2013
DOI: 10.1021/ja407225t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Ultrafast Quenching of the 3MLCT Luminescence in Ruthenium(II) Tris-bipyridyl Complexes via a 3dd State

Abstract: Ultrafast transient absorption spectroscopy serves to identify the (3)dd state as intermediate quencher state of the (3)MLCT luminescence in the non-luminescent ruthenium complexes [Ru(m-bpy)3](2+) (m-bpy = 6-methyl-2,2'-bipyridine) and [Ru(tm-bpy)3](2+) (tm-bpy = 4,4',6,6'-tetramethyl-2',2'-bipyridine). For [Ru(m-bpy)3](2+), the population of the (3)dd state from the (3)MLCT state occurs within 1.6 ps, while the return to the ground state takes 450 ps. For [Ru(tm-bpy)3](2+), the corresponding values are 0.16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
185
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(208 citation statements)
references
References 34 publications
17
185
0
6
Order By: Relevance
“…Precise identification of species A and B is not possible, but the initial ultrafast processes are likely to involve internal conversion from the optically excited (ligand-centered) state to the 1 MLCT, intersystem crossing to the 3 MLCT state, and (vibrational and solvent) relaxation of the 3 MLCT state. 77 For the TAA-ph-Ru 2+ dyad very similar transient absorption spectra are obtained ( Figure S1), but the kinetics analysis yields time constants that are different from those obtained for TAAtmb-Ru 2+ . Specifically, 0.9 ps, 1.5 ps, ∼4 ns, and >5 ns are found; the respective SADS of an A → B → C → D → E reaction sequence are shown in Figure S2.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 51%
“…Precise identification of species A and B is not possible, but the initial ultrafast processes are likely to involve internal conversion from the optically excited (ligand-centered) state to the 1 MLCT, intersystem crossing to the 3 MLCT state, and (vibrational and solvent) relaxation of the 3 MLCT state. 77 For the TAA-ph-Ru 2+ dyad very similar transient absorption spectra are obtained ( Figure S1), but the kinetics analysis yields time constants that are different from those obtained for TAAtmb-Ru 2+ . Specifically, 0.9 ps, 1.5 ps, ∼4 ns, and >5 ns are found; the respective SADS of an A → B → C → D → E reaction sequence are shown in Figure S2.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 51%
“…These observations suggest a basis for selecting Ru photosensitizers with lower energy 3 MLCT than 3 MC excited states: the 77 K MLCT emission maximum of the sensitizer should have a lower energy than the energy for breaking both Ru−ligand bonds along the weakest bonding axis. 21 The point for [Ru(bpy) 3 ] 2+ is based on 3 MC calculations reported by Sun et al, 15 and 77 K emission spectra reported by Thomas et al 21 The code numbers in panel A are from The Supporting Information is available free of charge on the…”
Section: ■ Conclusionmentioning
confidence: 99%
“…23 As these authors note, the only experimental observations that relate to the role of 3 MC states are based on the time difference between 3 MLCT absorption decay and ground state absorption recovery, complemented by density functional theory (DFT) calculations to demonstrate that 3 MLCT and 3 MC excited states are near in energy, that IC can greatly alter 3 MLCT lifetimes, and that the relative energies of these excited states can be stereochemically manipulated for some [Ru(PP) 3 ] 2+ , where PP = bipyridine (bpy) or a methyl-substituted bipyridine. 15 We have approached this problem using DFT modeling 18−21 of the triplet excited states in combination with emission spectroscopic observations. We use a contemporary version of Gaussian 24 that incorporates the Franck−Condon approximation, as developed by Barone and co-workers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…71 The present work underlines one more time that the same energy gap does not warrant similar radiationless rate constants, and that the nature of the states involved, including vibronic and relativistic effects, should be taken into account. [58][59][60] Finally, a detailed understanding of the dynamics of low-lying MC states is needed for elucidating their role in the relaxation cascades of transition metal complexes, 11,13,72 which in applications typically originate from one of high-energy CT states formed by absorption in the visible range.…”
Section: -mentioning
confidence: 99%